An analysis of neonatal mortality following gastro-intestinal and/or abdominal surgery in a tertiary hospital in South Africa - Siyotula, Thozama Violet (Division of General Surgery, 2022)
Background: The World Health Organisation estimates approximately 10% of neonatal deaths in sub-Saharan Africa and South Asia are due to congenital malformations. Neonatal mortality in the Republic of South Africa needs to be benchmarked against high income countries' (HIC) standard of care to identify means to reduce infant mortality, much of which is due to congenital anomalies amenable to surgical correction. Objectives: (1) Assess 30-day, 6-month and 12-month post-operative mortality for neonates operated for gastrointestinal and abdominal wall defects at a tertiary freestanding paediatric hospital in Western Cape, South Africa, over a 12-year period. (2) Ascertain the causes and risk factors associated with 30-day post-operative mortality. Method: A retrospective folder audit of all neonates that underwent gastrointestinal & abdominal wall surgery within the neonatal period at Red Cross War Memorial Children's Hospital (RCWMCH) during the 12-year period from 1 January 2007 to 31 December 2018. Results: The 30-day post-operative mortality rate was 73/762 (11%). Mortality was found in 9 conditions. An additional 57/762 patients (7%) died post-surgery between 30 days from surgery and 6 months of age. A further 34 patients (4%) died between 6 and 12 months of age. Mortality resulted from: sepsis (74%), palliation due to ultra-short bowel length (12%); in patients with necrotizing enterocolitis, intestinal atresia and malrotation with volvulus, ventilation associated pneumonia (10%), associated congenital cardiac lesions (3%) and intestinal failure associated liver disease (1%). Most neonates (69%) who died were prematurely born. Mean age at surgery was 10 days (median 6 days; interquartile range (IQR) 3-16) and mean age at death was 6 days (median 5 days; IQR 2-12; range 1-30). Nearly all patients who died were managed in the intensive care unit post-operatively (97%), with a median stay of 7 days (IQR 1-10) and overall hospital stay of 8 days (IQR2-12). Mortality in patients from referral hospitals more than an hour drive from RCWMCH was high (15/39, 38%). The odds ratio for death for patients with travel time over one hour from the referral hospital was 3.6 [95% confidence interval 1.8 to 7.3; z-statistic 3.6; p=0.0003]. The majority of surgical procedures in patients who died were for abdominal surgery 70/73 (96%). Surgery for necrotizing enterocolitis (NEC) had the greatest mortality (38%), followed by spontaneous intestinal perforation at (29%), gastroschisis (18%). Thirty-day mortality for oesophageal atresia, congenital diaphragmatic hernia and malrotation with volvulus was 9% each, followed by intestinal atresia at 8%, anorectal malformation (5%) and inguinal hernia (3%). No post-operative mortality was reported for Hirschsprung disease, choledochal malformation, hypertrophic pyloric stenosis, biliary atresia and omphalocele. Relook procedures were conducted for 37%, with the highest percentage of revision surgery for necrotizing enterocolitis at 42%. Abdominal compartment syndrome was noted post operatively in 15% patients. Significant modifiable risk factors for sepsis in patients who died were central lineassociated bloodstream infections (65%), respiratory tract infections (41%) and surgical complications [anastomotic breakdown (7%) and wound infection (24%)]. Conclusion: The 30-day post-operative mortality rate in this middle-income setting is similar to the overall mortality rate in HIC, despite excluding pre-operative mortality in this study. Prevention and improvement strategies for infection control are imperative to improve outcomes in surgical neonates, including optimizing timing of surgical intervention for bowel perforation or obstruction through timeous patient transfer for definite management and intensive care unit capacity optimization, central line care and post-operative infection surveillance. Liberal abdominal compartment pressure monitoring and delayed abdominal closure in selected patients may further reduce mortality. Addressing modifiable factors for morbidity and mortality in this vulnerable patient group is required for comparable outcomes to HIC.